Studi Kelengkapan Dokumentasi Pra Intra dan Pasca Anestesi di RSUD Dr. M. Ashari Pemalang - Susilawati, Evawani; Handayani, Rahmaya Nova; Suryani, Roro Lintang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Medical records have a function to maintain and provide information for all parties involved in providing health services to patients. Completeness of anesthesia medical records is an important key element of good and quality anesthesia service practice. The study aims to determine the completeness of pre, intra, and post-anesthesia documentation at RSUD Dr. M. Ashari Pemalang. This research method is descriptive quantitative with a sample of 93 medical record documents taken with probability sampling technique. Data was collected by observing medical record documents then recording the completeness of documentation using a checklist. The results showed that the completeness of pre-anesthesia medical record documentation was 94.6% on the pre-anesthesia assessment form and 91.4% on the pre-induction assessment form. The completeness of intra-anesthesia medical record documentation was 96.8% on the anesthesia report form and 93.5% on the intra-anesthesia monitoring form. The completeness of post-anesthesia medical record documentation was 91.4% on the post-anesthesia documentation form. This means that the completeness of pre-, intra- and post-anesthesia medical record documentation at RSUD Dr. M. Ashari Pemalang has not reached the hospital’s minimum service standard of 100%. It is necessary to monitor and evaluate the implementation of anesthesia medical record documentation so that the achievement results are in accordance with hospital service standards.